2003
DOI: 10.2174/1568026033392499
|View full text |Cite
|
Sign up to set email alerts
|

Traditionally-Used Antimalarials from the Meliaceae

Abstract: A quantitative ethnobotanical approach to antimalarial drug discovery led to the identification of Lansium domesticum Corr. Ser. (Meliaceae) as an important antimalarial used by Kenyah Dyak healers in Indonesian Borneo. Triterpenoid lansiolides with antimalarial activity were isolated from the bark and shown to have activity in both in vitro bioassays with Plasmodium falciparum, and in mice infected with P. berghei. A survey of African and tropical American Meliaceae led to further development of the limonoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 0 publications
1
48
0
6
Order By: Relevance
“…Other studies have shown toxic properties of limonoids on insect larvae [30,31]. More specifically, gedunin and some of its derivatives have been investigated for antimalarial, hepatoprotective, and antitumor properties [32][33][34]. Anti-inflammatory, analgesic, and antiallergic virtues of the oil have led to the development of pharmaceutical products [35].…”
Section: Propertiesmentioning
confidence: 99%
“…Other studies have shown toxic properties of limonoids on insect larvae [30,31]. More specifically, gedunin and some of its derivatives have been investigated for antimalarial, hepatoprotective, and antitumor properties [32][33][34]. Anti-inflammatory, analgesic, and antiallergic virtues of the oil have led to the development of pharmaceutical products [35].…”
Section: Propertiesmentioning
confidence: 99%
“…The Meliaceae are one of the most important tree families in tropical rain forests both ecologically and economically. Some trees are a major source of very valuable tropical hardwood timber such as mahogany, and members of the family are also used for oil, soap manufacture, insecticides, and medicines (Cheplogoi and Mulholland 2003;Omar et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro antimalarial activities have recently been reported for limonoids from other Meliaceae: bark and seeds of Khaya grandifolia (2), bark of Khaya senegalensis (13), leaves of Azadirachta indica (11), and Cedrela odorata wood (3). The most active limonoid, gedunin, isolated from Khaya grandifolia, Cedrela odorata, and Azadirachta indica (3,16), had a better in vitro activity than chloroquine against clones sensitive to chloroquine (15). Its in vitro activity evaluated against a chloroquine-resistant strain of P. falciparum (IC 50 ϭ 0.72 g/ml) was roughly equivalent to that of trichirubine A (12), but its in vivo activity, initially poor (3), might be improved: for example, when combined with chloroquine (2), by synergism with dillapiol, a cytochrome P-450 3A4 inhibitor, or preparation of a more stable compound (16).…”
mentioning
confidence: 99%